Essential Oils of Plants as Biocides againstMicroorganisms Isolated from Cuban and Argentine Documentary Heritage - Borrego, Sofía (2012)
Fil: Borrego, Sofía. Laboratory of Preventive Conservation. National Archive of the Republic of Cuba. Havana; Cuba